RESILIENCE OF SOCIAL WORKERS' PROFESSIONAL IDENTITY: INTERNATIONAL LESSONS AND UKRAINIAN CHALLENGES - СТОЛЯРИК, Ольга; СЕМИГІНА, Тетяна (Видавничо-поліграфічний центр “Київський університет”, 2025)
Background. The full-scale war in Ukraine has radically transformed the conditions of social work, posing new moral and professional challenges for specialists. There is a growing need to understand internal resources for maintaining stability and functionality. Professional identity is viewed as a key resource for individual and collective resilience, which is particularly relevant in wartime. The purpose of this study is to theoretically conceptualize professional identity within the framework of collective resilience, analyze its relationship with organizational conditions, and explore the concept of "professional identity resilience" and its formation practices. The study was conducted as a review within the qualitative interpretative paradigm, based on the analysis of 27 scientific publications (2005–2024) from international databases (Scopus, Web of Science, PsycINFO, Google Scholar). The search was conducted using keywords that reflected the connection between professional identity, resilience, war, and crisis. The analysis was conducted in accordance with the principles of thematic synthesis, with an emphasis on adapting to Ukrainian realities. Results. It was determined that professional identity is a multidimensional dynamic construct that encompasses role, values, community belonging, and social mission. The key element is 'commitment.' Professional identity resilience is the ability of a specialist to maintain values and motivation under stress and in crises. Its formation depends on personal experience, education, socialisation, reflection, mentoring, and organisational climate. The author proposes a conceptual model for the formation and maintenance of professional identity resilience in social workers (the interaction of internal and external factors, their connection with individual, professional and organisational resilience) and reveals the key stages and methods that contribute to the development of professional identity and its resilience throughout the professional career of a specialist, covering the pre-professional, educational, field practice, professional and growth stages through inclusion in the professional community. For Ukraine, these stages are critically important for laying value foundations, adapting specialists to war challenges through reflective practices, supervision, coaching, and developing professional solidarity and ethical leadership. Conclusions. The resilience of a social worker's professional identity is a critically important resource in current crisis conditions. Its formation requires a systematic, phased approach that integrates quality education, practical support, and institutional development. This will allow for the formation of adaptable, resilient specialists capable of effectively responding to the urgent needs of Ukrainian society and contributing to its recovery.

Вступ. Повномасштабна війна в Україні трансформувала умови соціальної роботи, ставлячи перед фахівцями нові виклики. Зростає потреба в розумінні внутрішніх ресурсів для збереження стійкості та функціональності. Професійна ідентичність розглядається як ключовий ресурс індивідуальної та колективної резилієнтності, що особливо актуально у воєнний час. Метою розвідки є теоретична концептуалізація професійної ідентичності в межах колективної стійкості, аналіз взаємозв'язку з організаційними умовами, а також дослідження концепції “professional identity resilience” та практики її формування. Дослідження здійснено у форматі оглядового дослідження в межах якісної інтерпретативної парадигми. Емпіричну основу становить аналіз 27 наукових публікацій, опублікованих у період 2005–2024 років та індексованих у міжнародних наукометричних базах Scopus, Web of Science, PsycINFO та Google Scholar. Відбір джерел здійснювався шляхом цільового пошуку за ключовими словами, що відображають взаємозв’язок професійної ідентичності, психологічної стійкості, війни та кризових умов. Аналітичну процедуру реалізовано відповідно до принципів тематичного синтезу, з акцентом на інтерпретацію отриманих результатів у контексті сучасних українських реалій. Результати. Визначено, що професійна ідентичність є багатовимірним динамічним конструктом, що охоплює роль, цінності, належність до спільноти та суспільну місію. Ключовим елементом є "відданість". Стійкість професійної ідентичності (professional identity resilience) – здатність фахівця зберігати цінності та мотивацію під стресом та у кризових ситуаціях. Її формування залежить від особистого досвіду, освіти, соціалізації, рефлексії, менторства та організаційного клімату. Запропоновано авторську концептуальну модель формування та підтримки стійкості професійної ідентичності соціального працівника (взаємодія внутрішніх і зовнішніх чинників, їхній зв'язок з індивідуальним, професійним та організаційним резилієнсом) та розкрито ключові етапи та методи, що сприяють розвитку професійної ідентичності та її стійкості протягом усього професійного шляху фахівця, що охоплює допрофесійний, освітній, етап польової практики, професійний етап та етап зростання через включення в професійну спільноту. Для України ці етапи критично важливі в сенсі закладення ціннісних основ, адаптації фахівців до викликів війни через рефлексивні практики, супервізію, коучинг, а також розвитку професійної солідарності та етичного лідерства. Висновки. Стійкість професійної ідентичності соціального працівника є критично важливим ресурсом у сучасних кризових умовах. Її формування вимагає системного поетапного підходу, що інтегрує якісну освіту, практичну підтримку та інституційний розвиток. Це дозволить сформувати адаптованих, резилієнтних фахівців, здатних ефективно відповідати на нагальні потреби українського суспільства та сприяти його відновленню.
СТІЙКІСТЬ ПРОФЕСІЙНОЇ ІДЕНТИЧНОСТІ СОЦІАЛЬНИХ ПРАЦІВНИКІВ: МІЖНАРОДНІ УРОКИ ТА УКРАЇНСЬКІ ВИКЛИКИ
Keywords: collective resilience; professional identity; professional training; resilience; social resilience; social work; stability of professional identity; traumatisation; колективна стійкість; професійна ідентичність; професійна підготовка; резилієнтність; соціальна резилієнтність; соціальна робота; стійкість професійної ідентичності; травматизація